Introducing The Theory Of The "Inclusive Diffusion" Approach To Inclusive Education And Its Prospects - Sh.K. Kobilova (Periodica Journal, 2023)
In this article, a new, modern and non-standard approach, i.e. "Inclusive Diffuse" scientific theory, the methodology, mechanism and possibility of its implementation, put forward by the author in the creation of a suitable process aimed at improving the quality and efficiency of inclusive education, stabilizing the socialization and integration of students with disabilities and perspectives are highlighted
Keywords: education; physical law; socialization